The ice queen : a novel - Neuhaus, Nele (Minotaur Books, 2015)
"The body of 92-year-old Jossi Goldberg, Holocaust survivor and American citizen, is found shot to death execution-style in his house near Frankfurt. A five-digit number is scrawled in blood at the murder scene. The autopsy reveals an old and unsuccessfully covered tattoo on the corpse's arm--a blood type marker once used by Hitler's SS. Pia Kirchhoff and Oliver Bodenstein are faced with a riddle. Was the old man not Jewish after all? Who was he, really? Two more, similar murders happen--one of a wheelchair-bound old lady in a nursing home, and one of a man with a cellar filled with Nazi paraphernalia--and slowly the connections between the victims becomes evident"--Amazon.com.